Combining the YOLOv5 and Grabcut Algorithms for Fashion Color Analysis of Clothing - Liu, Fenghua; Liu, Zhaoqi; Liu, Weiguang; Zhao, Hongsheng (2022 5th World Conference on Mechanical Engineering and Intelligent Manufacturing (WCMEIM), 2022)
The analysis and prediction of apparel fashion colors are very important for the production and sales activities of the apparel industry. In the field of fashion color analysis of apparel images, existing image algorithms have problems such as poor segmentation effects in complex backgrounds and poor data real-time. In this paper, the YOLOv5 algorithm is applied to garment detection, the histogram equalization is used to enhance the image of garment pictures, the KMeans clustering algorithm is used to get the approximate foreground area of the garment, the GrabCut algorithm is used to segment the image with the processed pictures to get the final foreground color area of the garment, and then the KMeans clustering algorithm is used to get the main color of the garment. thus analyzing the pattern between colors. The study of fashionable colors of clothing in video surveillance scenes has higher real-time data volumes, larger data capacities, and faster analysis speeds than the current research methods.